Legal Protection Against Children of Consanguineous Marriages - Ariany, Farida; Aminullah, Aminullah; Fitriatun, Erna (JUPE : Jurnal Pendidikan Mandala, 2025)
A secret marriage is considered invalid by the state, therefore, children born from this marriage are considered as children born out of wedlock. This is different from the religious perspective. This opinion is based on article 43 paragraph (1) of the Marriage Law which states that "Children born out of wedlock may only have a civil relationship with their mother and their mother's family. Therefore, a secret marriage will annul the rights of the wife and children. However, there are quite a few implementations of marriage in regions where the implementation of marriage is only based on religious law and customary law, without involving the Marriage Registrar so that this marriage is considered a secret marriage which often causes losses to the wife and children born. The lack of guarantees of civil rights as a result of a secret marriage results in the child not getting citizenship status, and the child only has a civil relationship with the mother and her mother's family, which in turn bears the burden of child maintenance costs.Married couples must comply with religious and state laws. In Islamic law, marriage must fulfill the pillars of marriage which include prospective husband, prospective wife, marriage guardian, two witnesses, ijab and kabul, while state law requires that the validity of the marriage must be registered in accordance with applicable laws. However, there are many implementations of marriage in regions where the implementation of marriage is only based on religious and customary laws, without involving Marriage Registrars so that this marriage is considered a secret marriage which often causes losses to the wife and the children born. The lack of guarantees of civil rights as a result of a secret marriage results in the child not getting citizenship status, and the child only has a civil relationship with the mother and her mother's family, which in turn bears the burden of child maintenance costs.